Effect of Genotype × Environment Interaction on Yield of Maize Hybrids in Greece Using AMMI Analysis - Nikolaos Katsenios; Panagiotis Sparangis; Dimitriοs Leonidakis; George Katsaros; Ioanna Kakabouki; Dimitrios Vlachakis; Aspasia Efthimiadou (Agronomy, 2021)
An increase in grain yield remains a major target for all involved in maize cultivation. In this study, five maize genotypes were evaluated in a two-year (2017 and 2018) field experiment that was conducted at six locations. Additive main effects and multiplicative interaction (AMMI) analysis was used to detect the narrow adaptations of genotypes in specific mega-environments and the positive interactions of genotypes (G) and environments (E). According to the results of ANOVA, the G × E interaction effect explained 80.36% of the variation, while G explained only 12.79% of the variation, with the remainder explained by E (6.85%). The AMMI model indicated that GEN2, GEN4, and GEN5 were the most suitable genotypes for the three mega-environments delineated. Furthermore, GEN4 was found to have a large positive interaction with the environments featuring the highest rain precipitation during the cultivation period, while GEN2 had a large positive interaction with environments where the mean monthly high temperature was over 34 °C, according to the climatic data during the cultivation period. Additionally, the four environments with slightly acidic pH had a positive interaction with all genotypes of the research, except GEN2.